A tactical-game approach and enhancement of metacognitive behaviour in elementary school students. (3rd March 2016) - Chatzipanteli, Athanasia; Digelidis, N.; Karatzoglidis, C.; Dean, R.
Abstract : Background : 'Teaching games for understanding' (TGfU) is a tactical-game approach to teaching, in which participants are learning via the processes intrinsic to the games themselves. Purpose : The aim of the study was to examine the effectiveness of a tactical-game model in promoting metacognitive behaviour in elementary-school students. Participants and settings : Seventy-one students aged 11–12 years were randomly assigned to an experimental group (13 boys and 16 girls) and a control group (19 boys and 23 girls). Research design : Teachers in the intervention classes applied the tactical-game approach (TGfU) in teaching volleyball. Within the control group, the technique-focus approach was applied. Data collection : Metacognitive behaviour was assessed pre and post-intervention via think-aloud protocols. Descriptive statistics showed that students from the experimental group made appreciable gains in metacognitive behaviour. Previous to the intervention programme 5.63% of students were categorized as high level in terms of metacognitive behaviour. After the intervention programme 22.53% were categorized at high level. Conclusions : The results imply that the tactical-game approach could improve metacognitive behaviour in physical education classes in elementary school.